Bivariate Topp-Leone family of distributions (2022)
The Topp-Leone family of univariate distributions has drawn considerable attention in recent years. In this article, we define a bivariate generalization of the Topp-Leone distribution. Moreover, we derive several results such as marginal and conditional distributions, joint moments, correlation coefficient, and Fisher information matrix. Furthermore, we derive the exact distributions of X + Y , X/(X + Y ) and XY when X and Y follow bivariate Topp-Leone distribution.